Quantification of Trace-Level Silicon Doping in AlxGa1–xN Films Using Wavelength-Dispersive X-Ray Microanalysis. (August 2021) - Spasevski, Lucia; Buse, Ben; Edwards, Paul R.; Hunter, Daniel A.; Enslin, Johannes; Foronda, Humberto M.; Wernicke, Tim; Mehnke, Frank; Parbrook, Peter J.; Kneissl, Michael; Martin, Robert W.
Abstract: Wavelength-dispersive X-ray (WDX) spectroscopy was used to measure silicon atom concentrations in the range 35–100 ppm [corresponding to (3–9) × 10 18 cm −3 ] in doped Al x Ga1– x N films using an electron probe microanalyser also equipped with a cathodoluminescence (CL) spectrometer. Doping with Si is the usual way to produce the n -type conducting layers that are critical in GaN- and Al x Ga1– x N-based devices such as LEDs and laser diodes. Previously, we have shown excellent agreement for Mg dopant concentrations in p -GaN measured by WDX with values from the more widely used technique of secondary ion mass spectrometry (SIMS). However, a discrepancy between these methods has been reported when quantifying the n -type dopant, silicon. We identify the cause of discrepancy as inherent sample contamination and propose a way to correct this using a calibration relation. This new approach, using a method combining data derived from SIMS measurements on both GaN and Al x Ga1– x N samples, provides the means to measure the Si content in these samples with account taken of variations in the ZAF corrections. This method presents a cost-effective and time-saving way to measure the Si doping and can also benefit from simultaneously measuring other signals, such as CL and electron channeling contrast imaging.